Maternal Diabetes and Autism Spectrum Disorders in the Offspring: A Review of Epidemiological Evidence and Potential Biologic Mechanisms - Bowers, PhD, Katherine; Zhang, MD, PhD, Cuilin (North American Journal of Medicine and Science, 2011)
Gestational diabetes is a common pregnancy complication whose prevalence is increasing among women of reproductive age and results in both short-and long-term adverse outcomes for the offspring. Hyperglycemia or other consequences of adverse maternal metabolic profiles in pregnancy may contribute to autism risk through several potential mediating mechanisms, such as inflammation, oxidative stress, and epigenetics. The present review aims to summarize recent studies exploring the association between maternal pre-gestational diabetes, gestational diabetes, obesity and autism spectrum disorders (ASD) in the offspring. We will also explore potential biologic mechanisms to explain the association between in utero exposure to a hyperglycemic environment and risk for ASD, including inflammation, oxidative stress and epigenetics. Considering the concurrent rise in obesity and diabetes in pregnancy, as well as the modifiable nature of these disorders, their associations with ASD and the underlying molecular mechanisms should be explored further.